The Taste of Peranakan Tionghoa in Listening to Indonesian and Chinese Music and Their Relation to Cultural Identity - Sari, Sulhizah Wulan; Adhi, Sukmono Bayu (Lingua Cultura, 2019)
This research discussed the taste of Peranakans Tionghoa in listening to Indonesian and Chinese music and its relation to cultural identity. The history of the settlements in Chinatown at Glodok, Jakarta, Indonesia, brought ethnic and cultural issues. Then, the assimilation was inadequate that caused the elimination of the original culture and finally form a new culture. This research questioned how the Peranakans Chinese cultural identity was formed and related to the taste of listening to Chinese and Indonesian music using Hallâ€™s perspective of cultural identity. A qualitative method was used to describe, explain, and analyze data. Data in the research consisted of observation and interview of the 30 Peranakans Tionghoa at Glodok, covering the area of mall, cafÃ©, and restaurant. The collected data were classified into similarities and differences from each aspect. The classification was linked to the three groups who preferred to listen to music and find their cultural identity. The result shows that the taste of Peranakan Tionghoa in listening to Indonesian and Chinese music depends on the elements and the function of music. Those aspects emphasize the language to understand what the song tells about. Further, the music could be an intermediary for cultural unification from both origins of (Chinese and Indonesia) who are fused to the relation of the cultural identity. Related to identity, Peranakans Tionghoa is becoming an identity.